FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS LEMBAGA PERKREDITAN DESA (LPD) DI KOTA DENPASAR - Putu Riska Wulandari (Paulus Journal of Accounting (PJA), 2020)
LPD performance measures can be seen from the LPD's ability to generate profits in a certain period and one of the most appropriate indicators or methods used to measure LPD financial performance is to use profitability ratios. The higher the ability to generate profits, it can be assumed to have a good level of health to be able to survive in competitive economic conditions. In order to achieve this assumption, the LPD must be able to use and manage all of its assets productively. The level of profitability of the LPD can be influenced by several factors, including the growth rate of the number of customers, cash turnover, capital adequacy, credit extended and credit risk which affects the level of profitability of the LPD. The research sample was 35 LPDs in the city of Denpasar which were carried out for three years of observation, namely as many as 105 samples. Determination of the sample in this study using purposive sampling. The data analysis used multiple linear regression analysis. The results of this study indicate that the number of customers, cash turnover, capital adequacy ratio, credit distribution have a positive effect on the profitability of LPDs in Denpasar City, while credit risk has a negative effect on the profitability of LPDs in Denpasar City.